A novel microfluidic valve controlledby induced charge electro-osmotic flow. (6th June 2016) - Wang, Chengfa; Song, Yongxin; Pan, Xinxiang; Li, Dongqing
Abstract: In this paper, a novel microfluidic valve by utilizing induced charge electro-osmotic flow (ICEOF) is proposed and analyzed. The key part of the microfluidic valve is a Y-shaped microchannel. A small metal plate is placed at each corner of the junction of the Y-shaped microchannel. When a DC electrical field is applied through the channels, electro-osmotic flows occur in the channels, and two vortices will be formed near each of the metal plates due to the ICEOF. The two vortices behave like virtual 'blocking columns' to restrain and direct the flow in the Y-channel. In this paper, effects of the length of the metal plates, the applied voltages, the width of the microchannel, the zeta potential of the non-metal microchannel wall, and the orientation of the branch channels on the flow switching between two outlet channels are numerically investigated. The results show that the flow switching between the two outlet channels can be flexibly achieved by adjusting the applied DC voltages. The critical switching voltage (CSV), under which one outlet channel is closed, decreases with the increase in the metal plate length and the orientation angle of the outlet channels. The CSV, however, increases with the increase in the inlet voltage, the width of the microchannel, and the absolute value of the zeta potential of the non-metal microchannel wall. Compared with other types of micro-valves, the proposed micro-valve is simple in structure without any moving parts. Only a DC power source is needed for its actuation, thus it can operate automatically by controlling the applied voltages.